Transcriptional Regulation: Molecules, Involved Mechanisms and Misregulation - Ciccodicola, Alfredo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Transcriptional regulation is a critical biological process involved in the response of a cell, a tissue or an organism to a variety of intra- and extra-cellular signals. Besides, it controls the establishment and maintenance of cell identity throughout developmental and differentiation programs. This highly complex and dynamic process is orchestrated by a huge number of molecules and protein networks and occurs through multiple temporal and functional steps. Of note, many human disorders are characterized by misregulation of global transcription since most of the signaling pathways ultimately target components of transcription machinery. This book includes a selection of papers that illustrate recent advances in our understanding of transcriptional regulation and focuses on many important topics, from cis-regulatory elements to transcription factors, chromatin regulators and non-coding RNAs, other than several transcriptome studies and computational analyses.